A DNA Methylation-based Epigenetic Signature for the Identification of Lymph Node Metastasis in T1 Colorectal Cancer. Issue 4 (15th April 2023) - Zhao, Yinghui; Peng, Fuduan; Wang, Chuanxin; Murano, Tatsuro; Baba, Hideo; Ikematsu, Hiroaki; Li, Wei; Goel, Ajay
Abstract : Objective: This study aimed to unravel the lymph node metastasis (LNM)-related methylated DNA (mDNA) landscape and develop a mDNA signature to identify LNM in patients with T1 colorectal cancers (T1 CRC). Background: Considering the invasiveness of T1 CRC, current guidelines recommend endoscopic resection in patients with LNM-negative, and radical surgical resection only for high-risk LNM-positive patients. Unfortunately, the clinicopathological criteria for LNM risk stratification are imperfect, resulting in frequent misdiagnosis leading to unnecessary radical surgeries and postsurgical complications. Methods: We conducted genome-wide methylation profiling of 39 T1 CRC specimens to identify differentially methylated CpGs between LNM-positive and LNM-negative, and performed quantitative pyrosequencing analysis in 235 specimens from 3 independent patient cohorts, including 195 resected tissues (training cohort: n=128, validation cohort: n=67) and 40 pretreatment biopsies. Results: Using logistic regression analysis, we developed a 9-CpG signature to distinguish LNM-positive versus LNM-negative surgical specimens in the training cohort [area under the curve (AUC)=0.831, 95% confidence interval (CI)=0.755–0.892; P <0.0001], which was subsequently validated in additional surgical specimens (AUC=0.825; 95% CI=0.696–0.955; P =0.003) and pretreatment biopsies (AUC=0.836; 95% CI=0.640–1.000, P =0.0036). This diagnostic power was further improved by combining the signature with conventional clinicopathological features. Conclusions: We established a novel epigenetic signature that can robustly identify LNM in surgical specimens and even pretreatment biopsies from patients with T1 CRC. Our signature has strong translational potential to improve the selection of high-risk patients who require radical surgery while sparing others from its complications and expense.